The effect of hyperbaric oxygen therapy on cognition, performance, proteomics, and telomere length—The difference between zero and one: A case report - Maroon, Joseph C. (Frontiers in Neurology, 2022)
Introduction Hyperbaric oxygen (HBO2) therapy has recently been suggested for the treatment of different brain injuries as well as for physical and cognitive enhancement. The author recently carried out a self-experiment to obtain objective information on the effects of HBO2 therapy on neurocognition, cardiopulmonary function, neuroimaging and its effect on novel biomarkers such as telomere length and proteomics. In the following case report, the author will present and discuss the results and the differences between zero and one. Methods This is a personal case report on a single subject, myself, who underwent a protocol of 60 daily HBO2 therapy sessions within 3 months. Pre- and post-therapy objective evaluation measured included computerized cognitive assessment, brain imaging, cardiopulmonary exercise test, physical assessments and blood tests including telomere length and proteomics. Results Neurocognitive results showed a 3.1–3.8% improvements in global cognitive function as well as all other cognitive function domains. In the perfusion MRI, there was a relative increase ranging from 43.3 to 52.3% in cerebral perfusion in various areas subserving memory, coordination, and visual motor cortex function. Similar improvements in cerebral perfusion were seen in the SPECT scans, which ranged from 8.79 to 16.12% increased perfusion in the temporal pole and entorhinal cortex subserving memory, as well as in the subcallosal area and lingual gyrus. MRI-DTI showed prominent increases in fractional anisotropy in several white matter areas including 9% in the body of the corpus callosum, 16.85% in for the fornix and 22.06% in the tapetum. In the physical domains, there were improvements in both anaerobic threshold, exercise endurance, muscle strength, gait speed and grip strength in the 7–15% range. The telomeres length was doubled and clusters of inflammatory proteins dropped around the 40th session and remained low at the 60th session. Conclusion The difference between zero and one in this single case study of HBO2 therapy confirmed improvement in objective biomarkers which measured cognition, memory, brain processing speed, athletic performance and neuroimaging modalities measuring cerebral perfusion, blood flow and tractography. Additional studies with larger sample size and randomized clinical trials using similar biomarkers are needed to confirm the results and to delineate the longevity of these improvements.